Abra os olhos para o banco dos abrolhos: percepção ambiental, territorialidade e conflitos na ótica da pesca artesanal de Caravelas a Nova Viçosa, Bahia, Brasil - Marques, Pedro Henrique Dias (2020)
The Abrolhos Bank concentrates the largest Brazil's marine biodiversity and a range of actors using the territory. The objective of this research was to understand the historical transformati ons, economic and environmental factors that influence the territoriality of artisanal fishers of Caravelas and Nova Viçosa in the last 60 years. For this, I used the observation participant, semi structured interviews, focus groups and participatory mappi ng, beyond the study of existing historical / technical documents. Since the 1970s this territory had an intense naval traffic, with the entrance of large ships that were supplied by the Bahia Minas Railroad. The sea, the reefs, the wrecks and Natural reso urces are elements that compose the cultural heritage of the region. The territory has undergone a series of transformations and artisanal fishermen consider dredging, marine traffic of eucalyptus, sedimentation and bleaching of coral reefs, predatory fish ing, disorderly tourism, and most recently one of the largest environmental disasters Samarco Mining Company as the main environmental problems. Indeed, the information generated demonstrates how traditional knowledge of artisanal fishermen is essential fo r the understanding of the social and environmental transformations, through which the territory contributes to the production of interdisciplinary knowledge of the region that concentrates the largest marine biodiversity in the entire South Atlantic.